Phylogeography of Tridentiger bifasciatus (Gobiidae) in the Northwestern Pacific - Wang, Junjie; Hsu, Kui-Ching; Chen, Yue-Hua; Zhao, Jun; Tang, Wen-Qiao; Liu, Dong; Yang, Jin-Quan; Lin, Hung-Du (Frontiers in Ecology and Evolution, 2022)
The shimofuri goby (Tridentiger bifasciatus) is native to marine, brackish and fresh waters along the coasts of the northwest Pacific. Our study examined the population genetic structure, diversity and demography of T. bifasciatus in the China Seas, including Yellow Sea, East China Sea and South China Sea, using the sequences of mitochondrial DNA [mtDNA cytochrome b (cyt b) gene and d-loop region] and nuclear DNA [nuDNA ryanodine receptor 3 (Ryr3) gene]. The mtDNA data set revealed a significant population differentiation, but the nuDNA data set displayed the absence of genetic differentiation. The discordance between these two data sets was accounted for by population admixture, selection and incomplete lineage sorting. Although the mtDNA and nuDNA displayed a discordant population structure, these genetic markers revealed the same population history: (1) the populations retreated into two refugia during glaciations; and (2) the populations declined recently. Our study revealed that after glaciations, the re-flooding in Taiwan Strait did not shape the migrations of southern lineage form South China Sea to East China Sea; and displayed that two mtDNA lineages have diverged before they migrated southward during glaciations. These results offer important resources for the further study of conservation genetics.